Clinical effectiveness of symptomatic therapy compared with standard step-up care for the treatment of low-impact psoriatic oligoarthritis: the two-arm parallel group randomised POISE feasibility study. (November 2021) - Rombach, Ines; Tucker, Laura; Tillett, William; Jadon, Deepak; Watson, Marion; Francis, Anne; Sinomati, Yvonne; Dutton, Susan J; Coates, Laura C
Introduction: In psoriatic arthritis (PsA), treatment recommendations support first-line use of disease-modifying antirheumatic drugs (DMARDs). There are few treatment strategy trials, and no previous studies have investigated tailored treatment choice by disease severity. Studies in oligoarthritis (<5 inflamed joints) are limited but have suggested that some can be managed without DMARDs, preventing unnecessary side effects. This study aimed to assess the feasibility and acceptability of a study comparing standard DMARD treatment against symptomatic therapy in patients with mild psoriatic oligoarthritis. Methods: This trial was embedded within the MONITOR-PsA cohort, which uses a Trials Within Cohorts (TWiCs) design. Patients with newly diagnosed psoriatic oligoarthritis, with low disease activity (PASDAS ⩽ 3.2) and the absence of poor prognostic factors [C reactive protein (CRP) < 5 mg/dL, HAQ < 1, no radiographic erosions] were randomised open-label to either standard care with 'step-up' DMARD therapy or to symptomatic therapy with nonsteroidal anti-inflammatory drugs (NSAIDs) and local corticosteroid injections to inflamed joints. Key outcomes were the proportion of eligible cohort patients, consent and study completion rate. Results: Over the 15-month study period, only one eligible patient was randomised. Although oligoarthritis patients represented 45% of patients in this early PsA cohort, the majority did not have mild disease (24% raised CRP, 51% moderate disease activity, 13% radiographic damage and/or poor function). Of those meeting trial inclusion criteria, many patients refused treatment in the observational cohort prior to an invitation into the trial as they did not wish to be treated with DMARDs. Conclusion: The study was not feasible as designed. Oligoarthritis represents around half of initial PsA presentations, but the majority starting therapy have high-impact disease. A small proportion have mild oligoarticular disease but many are not keen on treatment with DMARDs, given the potential side effects of these medications. Further research is needed to support evidence-based treatment in this subgroup. Trial registration number: – ClinicalTrials.gov (NCT03797872) and EudraCT (2018-001085-42).